Etiopathogenesis of “bladder outlet obstruction” in the female: inability of pelvic muscles to sufficiently open urethra - Petros, Peter; Liedl, Bernhard; Wenk, Maren; Palma, Paolo (Urologia internationalis, 2025)
Background: Historically, opening the bladder neck and urethra for evacuation has been solely by detrusor contraction with “urethral relaxation.” Summary: We present a change in thinking based on experimental research and clinical practice, human and animal: the urethra is opened externally immediately prior to detrusor contraction by posterior pelvic floor muscles contracting against competent uterosacral ligaments (USLs). A binary feedback control system (EITHER open OR closed) with neurological and peripheral musculo-ligamentous components is presented. Three oppositely acting muscle vectors contract against suspensory ligaments to close urethra distally and at bladder neck; relaxation of the forward closure vector allows the two posterior muscles to contract against USLs to open the posterior urethral wall prior to micturition. Whatever the anatomical cause of bladder emptying difficulties, neurological, muscle damage, ligament damage, urethral obstruction, inability of the pelvic muscles to externally open the urethra means the detrusor must contract against an unopened urethra which presents a high resistance to flow. This resistance is perceived by the patients as “bladder outlet obstruction.” Collagen damage during birthing, or breakdown after the menopause, makes ligament damage the most vulnerable part of the female micturition system. Treatment depends on reinforcing USLs as the contractile point for the posterior opening muscles: in premenopausal women by squatting-based exercises; in older women by mechanical support of USLs by pessary, or surgical USL repair. Key Message: A change in thinking: posterior pelvic muscles contract against a firm USL to open posterior urethral wall prior to micturition (video https://www.youtube.com/watch?v=nK0CQmaS-5E&t=7s).